Fundamentalisme Keagamaan dalam Perspektif Kebudayaan - Mudjahirin Thohir (Analisa: Journal of Social Science and Religion, 2010)
Religion becomes reference of civilized value system which is played and plays to underlie pattern of community’s act. In this case, religion as knowledgesystem And believe systemReally depends on a result of interpretation on religious symbols. As a result, in each religion there will be variety of understanding, attitude, and respond toward their problems. One of those is fundamentalism view. Fundamentalist sees Islam is not only religious doctrine which directs human being in spiritual aspect, but also Islam Develops state system.To implement that view they sometimes commi radica action and violence. This writing tries to explore the phenomena of fundamentalism in the cultural perspective.   Keywords : Fundamentalism, Cultural